Factors associated with human papillomavirus infections among women living with HIV in public health facilities in Western Oromia, Ethiopia - Mulatu Abdi; Afework Tamiru; Temesgen Tilahun; Gemechu Tiruneh; Meseret Belete Fite (BMC, 2024)
Abstract Background Human Papillomavirus infection (HPV) is among the most common sexually transmitted infections with the highest incidence and prevalence worldwide. HPV has been established as the main cause of cervical cancer and remains a public health problem globally. In Western Oromia, Ethiopia cervical screening remains a major issue because of limited resources, and shortage of HPV testing technology. As a result, the prevalence of HPV and associated factors remain unknown among HIV-positive women. This study aimed to assess the prevalence of HPV and associated factors among women living with HIV attending Antiretroviral Therapy (ART) services in public health facilities of East Wollega and West Showa Zones, Ethiopia, 2022. Method Using a cross-sectional study design, a total of 415 women ≥ 18 years old were enrolled using systematic random sampling from five public health facilities. Cervical specimens were collected by a trained nurse from April 01 2022, to May 30, 2022, and tested at Nekemte Public Health Research and Referral Molecular Biology, a certified/accredited laboratory for HPV-DNA Polymerase Chain Reaction by expertise using Abbott m2000rt-PCR assays. Finally, Epi data version 4.6 was used for data entry and SPSS version 24.0 were used for data cleaning and analysis, and frequencies and prevalence of HPV were computed. Variables were identified using the multivariable model and statistically significant associations of variables were determined based on the adjusted odds ratio (AOR) with its 95% CI and P-value < 0.05 to determine the strength of association. Result The prevalence of HPV was 30.4% [95% CI: 26.0, 34.9]. Of HPV-infected women, 11.9% were positive for HPV-16, 9.5% for HPV-18, and 65.9% were positive for other hr-HPV . The odds of HPV infection among women aged beyond 48 years are 2.85 times the odds of HPV among people who were aged 18-27(AOR = 2.85, 95% CI: 1.16, 5.58). The odds of HPV infection among women who had three or more sexual partners is 4.12 times the odds of HPV infection among women with a single sexual partner(AOR = 4.12, 95% CI: 2.34-8.62). The odds of HPV infection among women who didn't use condom during sexual intercourse are 4.73 times the odds of HPV among women who used condom during sexual intercourse. (AOR = 4.73, 95% CI: 1.98-9.33). The odds of HPV infection among women who had history of is 4.52 times the odds of HPV infection among women with no history of abortion. [AOR = 4.52, 95% CI: 2.04, 6.89] The odds of HPV infection among women with history of Sexually Transmitted Infection (STI) 3.62 times the odds of HPV among women with no history of STI (AOR = 3.62, 95%CI: 1.75, 5.83). The odd of HPV among women with abnormal vaginal discharge is 3.31 times the odds of the disease among women with normal vaginal discharge [AOR = 3.31, 95% CI: 2.87,7.35). Conclusion and recommendation The prevalence of HPV infection among HIV-infected women was high in the study area. Given the above-associated factors, we recommend that the stakeholders integrate HPV prevention strategies into HIV /AIDS services. Furthermore, the study has provided essential information about the HIV link with hr-HPV infections, which may explain the high prevalence among HIV-infected women. This can contribute to policy development and planning of prevention strategies incorporating HPV infection prevention especially among youth and HIV-infected people.